Analysis of Price, Taste, and Service Quality on Purchase Decisions for Bandrek Drink in Rantauprapat - Muhammad Ridho Siregar; M. Ali Al Ihsan; Marlina Siregar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
In the business world, competition is an absolute must for every business actor, therefore, business actors need to design the right strategy to attract buyers to buy the products offered. Price, taste and quality of service of a product are some of the factors that influence consumer decisions to make purchases. This study aims to determine the effect of price, taste and quality of service on consumer purchasing decisions for bandrek drinks in Rantauprapat. The population in this study were all consumers of bandrek drink shops in Rantauprapat. The study used multiple linear regression tests. The results of the study showed that the variables of price, taste and quality of service simultaneously had a strong and unidirectional influence on consumer purchasing decisions for bandrek drinks. Price, taste and quality of service partially had a strong and unidirectional influence on consumer purchasing decisions for bandrek drinks.